Portable electronic vision enhancement systems in comparison with optical magnifiers for near vision activities: an economic evaluation alongside a randomized crossover trial. Issue 5 (29th September 2016) - Bray, Nathan; Brand, Andrew; Taylor, John; Hoare, Zoe; Dickinson, Christine; Edwards, Rhiannon T.
Abstract: Purpose: To determine the incremental cost‐effectiveness of portable electronic vision enhancement system (p‐EVES) devices compared with optical low vision aids (LVAs), for improving near vision visual function, quality of life and well‐being of people with a visual impairment. Methods: An AB/BA randomized crossover trial design was used. Eighty‐two participants completed the study. Participants were current users of optical LVAs who had not tried a p‐EVES device before and had a stable visual impairment. The trial intervention was the addition of a p‐EVES device to the participant's existing optical LVA(s) for 2 months, and the control intervention was optical LVA use only, for 2 months. Cost‐effectiveness and cost‐utility analyses were conducted from a societal perspective. Results: The mean cost of the p‐EVES intervention was £448. Carer costs were £30 (4.46 hr) less for the p‐EVES intervention compared with the LVA only control. The mean difference in total costs was £417. Bootstrapping gave an incremental cost‐effectiveness ratio (ICER) of £736 (95% CI £481 to £1525) for a 7% improvement in near vision visual function. Cost per quality‐adjusted life year (QALY) ranged from £56 991 (lower 95% CI = £19 801) to £66 490 (lower 95% CI = £23 055). Sensitivity analysis varying the commercial price of the p‐EVES device reduced ICERs by up to 75%, with cost per QALYs falling below £30 000. Conclusion: Portable electronic vision enhancement system (p‐EVES) devices are likely to be a cost‐effective use of healthcare resources for improving near vision visual function, but this does not translate into cost‐effective improvements in quality of life, capability or well‐being.